2018
DOI: 10.4103/ijo.ijo_289_18
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of vitrectomy under topical anesthesia in an office-based setting

Abstract: Purpose:The purpose of this study was to evaluate the feasibility and safety of office-based vitreoretinal procedures.Methods:Patients undergoing primary elective pars plana vitrectomy were elected for surgery in an office-based setting (performed in a minor procedure room under topical anesthesia [TA] and oral anxiolysis). Rates of surgical objective achievement, surgical timing, and comfort were recorded to evaluate feasibility. Intraoperative and postoperative adverse events were assessed to evaluate safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Due to the absence of akinesia and the potential for limited patient cooperation, we suggest that (1) the two-step anesthesia method should be used in carefully selected cases and (2) the surgeon must be well experienced in vitrectomy. It has to be kept in mind that despite the perceived risk of akinesia, application of topical anesthesia alone also results in lack of akinesia but is unlikely to cause sight-threatening complications during cataract surgery [33], vitrectomy [20, 21, 27, 28, 32, 34, 35], combined phacoemulsification and vitrectomy [29], or vitrectomy-related procedures, like fluid-gas exchange for open macular hole after vitrectomy [36]. A 2-year prospective study comparing lidocaine 2% jelly versus peribulbar anesthesia for 25- and 23-gauge sutureless vitrectomy also indicated that lack of akinesia did not prevent a successful surgical result [37].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Due to the absence of akinesia and the potential for limited patient cooperation, we suggest that (1) the two-step anesthesia method should be used in carefully selected cases and (2) the surgeon must be well experienced in vitrectomy. It has to be kept in mind that despite the perceived risk of akinesia, application of topical anesthesia alone also results in lack of akinesia but is unlikely to cause sight-threatening complications during cataract surgery [33], vitrectomy [20, 21, 27, 28, 32, 34, 35], combined phacoemulsification and vitrectomy [29], or vitrectomy-related procedures, like fluid-gas exchange for open macular hole after vitrectomy [36]. A 2-year prospective study comparing lidocaine 2% jelly versus peribulbar anesthesia for 25- and 23-gauge sutureless vitrectomy also indicated that lack of akinesia did not prevent a successful surgical result [37].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We read with great interest the article titled “Feasibility and safety of vitrectomy under topical anesthesia in an office-based setting” by Trujillo-Sanchez et al . [1] This is an interesting study highlighting that 27-Gauge vitrectomy surgeries can be performed as an office procedure under topical anesthesia without complications.…”
mentioning
confidence: 99%
“…We appreciate the authors for their keen interest in our article. [1] We cautiously analyzed their observations and concerns about 27-gauge vitrectomy procedures in an office-based setting[2] and we have the following comments. First, we consider that office-based vitrectomy under topical anesthesia is not only safe for vitreous floaters but these procedures could be excellent tools for prompt, cost-effective evaluation in macular interventions; however, just in a selected group of patients.…”
mentioning
confidence: 99%